Lead(II)-Selective Electrode Based on Dibenzodiaza-15-crown-4 - Reza Pouretedal, Hamid; Hossein Keshavarz, Mohammad (Asian Journal of Chemistry, 2016)
A PVC-based membrane of dibenzodiaza-15-crown-4 reveals a Nernstian potentiometric response for Pb2+ over a wide linear range (5.0 × 10–6–1.0 × 10–2 mol/L) with detection limit of 3.5 × 10–6 mole/L. It has a response time of about 15 s and can be used for at least 3 months without any divergence. The proposed membrane sensor revealed good selectivity for Pb2+ over a wide variety of alkali, alkaline earth and transition metal ions. The electrode was used as an indicator electrode in potentiometric titration of lead.